An efficiency model for accounting information system that affect of competitive advantage of SMEs in three southernmost provinces of Thailand. - Namburi, Nantharat (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research used a mixed method including 3 objectives (1) To compare the competitive advantage of business classified by category and registered capital of SMEs in the business three southernmost provinces of Thailand. (2) To study the influence of efficiency model for accounting information system that affect of competitive advantage of SMSs in three southernmost provinces of Thailand (3) To study the direction of creating efficiency for accounting information system that affect of competitive advantage of SMSs in three southernmost provinces of Thailand includes the study of the opportunities and obstacle to success from that direction. The population used in this research include Chief Executives of accounting business in three southernmost provinces of Thailand, the number of people using calculation 3,771 by Taro Yamane deviation 0.05 sample size of 362 people using quota sampling. In target group in-depth interviews audience number 8 the list using the select specific examples the data collected through questionnaires the content validity and reliability. The statistical analysis of the data consists of hundreds of value, mean, standard deviation and One-way analysis of variance and path analysis with structural equation and in-depth interview the results from the interviews were analyzed the content. The research found that the majority of respondents were female (56.63%) , during 31-40 years (62.15%) , Education bachelors degree graduate (69.06%) work Experience 6-10 years (35.36%) The business category commercial sector activity (49.72 %) and registered capital of 10-30 million baht (62.98%). The results showed that answering the research objective response: 1. Competitive advantage of business no difference was statistically significant when classified by type of business but competitive advantage of business difference statistically significant when the classification of the registered businesses SMEs in three southernmost provinces of Thailand. 2. The factors affect of efficiency for accounting information system for business SMEs in three southernmost provinces of Thailand consist of the specific characteristics of the user (Γ=0.22) participation of users (Γ=0.11) organizational structure (Γ=0.18) support of senior management (Γ=0.58) and quality of accounting information system (Γ=0.26). The factors that result in indirect competitive advantage of your business SMEs in three southernmost provinces of Thailand consist of characteristics of the user (Γ=0.20) participation of users (Γ=0.10) organizational structure (Γ=0.17) support of senior management (Γ=0.53) and quality of accounting information system (Γ=0.24) An efficiency for accounting information system that affect of competitive advantage of SMEs in three southernmost provinces of Thailand (β = 0.92) 3. The result direction of creating efficiency for accounting information system that affect of competitive advantage of SMEs in three southernmost provinces of Thailand There are many aspects due to the three southernmost provinces of Thailand area in contact with the country, Malaysia to get a discount on income tax and increase welfare and other entrepreneurs. Again, all weather events, make rivals make less outside of it. If it will increase the potential for competitive advantage of SMEs in business district, the three southernmost provinces of Thailand should be performed starting from the development potential of entrepreneurship, knowledge management, process, and store its own companies that there should be a structured organization, however, is to appropriate management using related technologies and promotion of entrepreneurship, the global standard for product development, manufacturing, certification marks are standard. There are a variety of distribution channels network management for customers presents a full range of services. The quality Managed aggressively for new customers and services that impress customers, so the direction of making efficiency for accounting information system that affect of competitive advantage of SMEs in three southernmost provinces of Thailand to create the accounting personnel to the market in three southernmost provinces as an opportunity to create jobs are scarce. Promote understanding and projecting the benefits and value to the business. If the accounting information used and the opportunities that will result from the completion thereof to recognize the context of present enterprise and can be edited have been prepared, or to set out strategies to meet competition in the market section of barrier is the attitude and perception of entrepreneurs about information technology, lack of holistic vision makes the lack of understanding of the application of information technology to benefit. Article history : Received 5 May 2018 Revised 22 August 2018 Accepted 30 August 2018 SIMILARITY INDEX = 1.05